From cowrie to cypto: Blockchain and the future of money - Raghavan, T.C.A. Sharad (Westland Publications Pvt. Ltd., 2020)
This book explains what blockchain is, how it works, what it has to don with cryptocurrencies, and what it means for companies and governments. It also discuss how this is different from any form of money we have known so far- its advantages as well as the dangers, and the best way to manage it.